The use of supplementary materials in EFL clases: a comparative analysis of public and private high schools - Jara García, Catalina de Lourdes (2011)
The present study explores the use of supplementary material in EFL classes in Public and Private high schools. The main purpose of this research is to determine the frequency of use of these teaching aids. The study was conducted in Quito, Ecuador. The sample included 174 adolescents ranging between 12 to 15 years of age that belonged to the 8th, 9th, and 10th grades, 6 English teachers both male and female; three from the public and three from the private high school.